Comparative evaluation of sealing ability of three different materials as barriers to coronal microleakage in root-filled teeth: An In Vitro study - Mahima S Jain; Mukesh Paliwal; Manish Sundesha; Sultan Abdulrahman Almalki; AlBandary H Al Jameel; Inderjit M Gowdar; Sugandha Arya (Wolters Kluwer Medknow Publications, 2024)
Aim: To compare the sealing ability of three different materials when used as postendodontic restoration barriers to coronal microleakage in root-filled teeth. Materials and Methods: In the present study, 60 single-rooted mandibular premolars with single canals were selected. After endodontic treatment was done with protaper files, they were divided into three groups of 20 teeth each, which were restored with Zirconomer (Group I), Hi-Dense (Group II), and Surefil composite (Group III), respectively. After storing in artificial saliva for 10 days, all teeth were then immersed in Rhodamine 6G fluorescent dye. Teeth were then sectioned buccolingually in a longitudinal direction. The coronal microleakage was measured in both halves under a fluorescence microscope and images were taken with a digital camera. Data obtained from the study in the form of scoring as per specific criteria was subjected to statistical analysis. Result: Results of the study showed that the minimum amount of coronal microleakage was seen in Group II restored with Hi-Dense followed by Group III restored with Surefil Composite and the maximum amount of coronal microleakage was seen in Group I restored with Zirconomer. Conclusion: On the basis of the results of the present study, it may be concluded that Hi-Dense showed better coronal sealing ability in access cavities. Surefil composite exhibited coronal microleakage less than Zirconomer but more than Hi-Dense.